Increase in the frequency of lower extremity venous reflux in male patients with hypertension receiving combination of an angiotensin-converting enzyme inhibitor and a calcium channel blocker - S. V. Letyagina; V. M. Baev; T. Yu. Agafonova (Кардиоваскулярная терапия и профилактика)
Aim. To study the effect of combined antihypertensive therapy (AHT) with an angiotensin-converting enzyme (ACE) inhibitor and a calcium channel blocker on the parameters of lower extremity venous reflux in males with hypertension (HTN).Material and methods. The study involved 46 men 30-50 years old with uncontrolled HTN, among whom 23 patients with chronic venous disease (CVD) were identified. The dynamics of the rate, temporal and velocity parameters of lower extremity venous reflux was analyzed for a 14-15-day period using combined AHT (lisinopril, 10 mg/day; amlodipine, 5 mg/day). Reflux was assessed at rest by ultrasound of symmetric superficial, deep and perforator veins.Results. As a result of treatment, 40 patients achieved the first target office systolic blood pressure (BP) level (<140 mm Hg). Of these, there were 21 and 19 hypertensive patients with and without CVD, respectively. Blood pressure decrease was accompanied with an 86% increase in the total number of venous refluxes (p=0,009). Analysis of the duration and velocity of reflux blood flow in 46 patients showed no differences. In hypertensive patients without CVD, the total number of refluxes increased by 144% during the treatment period (p=0,021). Among patients with CVD, no significant dynamics of the reflux rate was recorded (p=0,213). There were no differences in the temporal and velocity parameters of refluxes after treatment between patients with and without CVD.Conclusion. A decrease in blood pressure in men with uncontrolled HTN with a combined AHT with an ACE inhibitor and a calcium channel blocker is associated with an 86% increase in the total number of lower extremity venous refluxes. The increase is due to a significant (2,4 times) increase in the number of refluxes in patients without external signs of CVD and is not associated with the duration and velocity of reflux blood flow after AHT.